2010
DOI: 10.1103/physrevlett.105.133201
|View full text |Cite
|
Sign up to set email alerts
|

Cold Heteronuclear Atom-Ion Collisions

Abstract: We study cold heteronuclear atom-ion collisions by immersing a trapped single ion into an ultracold atomic cloud. Using ultracold atoms as reaction targets, our measurement is sensitive to elastic collisions with extremely small energy transfer. The observed energy-dependent elastic atom-ion scattering rate deviates significantly from the prediction of Langevin but is in full agreement with the quantum mechanical cross section. Additionally, we characterize inelastic collisions leading to chemical reactions at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
190
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(202 citation statements)
references
References 27 publications
11
190
1
Order By: Relevance
“…The inelastic collisions can result in either charge exchange or molecular ion formation and, in order to determine a detailed mechanism, mass spectrometry [5,15,16] of the reaction products is performed following the inelastic collisions. In these trials, a pure Ca + ion cloud consisting of ∼400 ions is mixed with Li atoms for 4 s. Subsequently, an oscillating electric field is applied to one of the ion trap electrodes to excite the radial motions of the ions.…”
Section: Resultsmentioning
confidence: 99%
“…The inelastic collisions can result in either charge exchange or molecular ion formation and, in order to determine a detailed mechanism, mass spectrometry [5,15,16] of the reaction products is performed following the inelastic collisions. In these trials, a pure Ca + ion cloud consisting of ∼400 ions is mixed with Li atoms for 4 s. Subsequently, an oscillating electric field is applied to one of the ion trap electrodes to excite the radial motions of the ions.…”
Section: Resultsmentioning
confidence: 99%
“…Hybrid ion-atom systems are of great interest [7] since these are inherently strongly interacting systems with a longer-range potential and inelastic processes can be studied. Recently, these systems have been explored considering two-body collisions, in which both collision partners are translationally cold [8], and on the many-body level [9], where the sympathetic cooling of the ion with ultracold atoms was observed. The study of these systems in the quantum regime can be applied to hybrid atom-ion devices [10] and in addressing fundamental many-body effects of ionic impurities, * hlamb01@qub.ac.uk.…”
Section: Introductionmentioning
confidence: 99%
“…In recent experiments [8,9,18], a single trapped ion of 174 Yb + in a Paul trap was immersed in a condensate of neutral 87 Rb atoms confined in a magneto-optical trap. A study of charge-transfer cross sections showed that the simple classical Langevin model was inadequate to explain the reaction rates [9].…”
Section: Introductionmentioning
confidence: 99%
“…Renewed interest in QDT for −C 4 /r 4 polarization potential has arisen with the emergence of cold ion-atom [11][12][13][14][15][16][17][18][19][20] and ion-molecule interactions and reactions [21][22][23][24][25][26]. For such heavier systems, the QDT takes on a different magnitude of importance for three primary reasons.…”
Section: Introductionmentioning
confidence: 99%